Investigation of wind characteristics and wind energy potential in Kirklareli, Turkey - Bayulken, Ahmet; Bekdemir, Sukru; Gokcek, Murat (Elsevier BV, 2007)
Abstract Utilization of wind energy as an energy source has been growing rapidly in the whole world due to environmental pollution, consumption of the limited fossil fuels and global warming. Although Turkey has fairly high wind energy potential, exploitation of the wind energy is still in the crawling level. In the current study, wind characteristics and wind energy potential of Kirklareli province in the Marmara Region, Turkey were analyzed taking into account the wind data measured as hourly time series. The wind data used in the study were taken from Electrical Power Resources Survey and Development Administration (EIEI) for the year 2004. The measured wind data were processed as annual, seasonal and monthly. Weibull and Rayleigh probability density functions of the location are calculated in the light of observed data and Weibull shape parameter k and scale parameter c are found as 1.75 and 5.25 m/s for the year 2004. According to the power calculations done for the site, annual mean power density based on Weibull function is 138.85 W/m2. The results indicate that investigated site has fairly wind energy potential for the utilization.